1984
DOI: 10.1093/ageing/13.5.299
|View full text |Cite
|
Sign up to set email alerts
|

Age and the Daily Dose of Thyroxine Replacement Therapy for Hypothyroidism

Abstract: The initial prescriptions and later adjustments of thyroxine (T4) replacement have been analysed in 2246 hypothyroid patients who have been monitored by a thyroid follow-up register for a mean period of 6 years (range 1-13 years). In 465 (21%) patients of 65 years or over, initial T4 doses were on average only 20 micrograms lower than in younger patients. However, only 40% of the elderly were taking 200 micrograms of T4/day or more, compared with 60% of the younger patients. Over 10 years, the predicted propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Several studies have suggested that advancing age leads to a decreased LT 4 dose requirement (9,(25)(26)(27)(28), but most of these studies did not include IBW and gender in their analyses. Only three studies included gender (25,26,28) and these studies either documented the age-related decline in LT 4 dose in men only (26), showed the effect in only men and menopausal women (25), or were unable to separate the effects of age and gender (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that advancing age leads to a decreased LT 4 dose requirement (9,(25)(26)(27)(28), but most of these studies did not include IBW and gender in their analyses. Only three studies included gender (25,26,28) and these studies either documented the age-related decline in LT 4 dose in men only (26), showed the effect in only men and menopausal women (25), or were unable to separate the effects of age and gender (28).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of patients with hypothyroidism due to Hashimoto's thyroiditis or radioiodine ablation of Graves' disease requires lesser doses of LT 4 than treatment of patients who have a complete absence of thyroid tissue (4,6). Other factors implicated in modifying LT 4 dose requirement include medications altering thyroxine binding or metabolism (23,24) and patient age, with dose requirements decreasing with increasing age (9,(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…Although this seems to be an easy goal, previous studies have shown that approximately 20% of individuals with hypothyroidism, including those with low-risk thyroid cancer, are over-treated, and almost the same percentage are under-treated (5)(6)(7)(8)(9)(10)(11)(12). Despite the generally held belief that iatrogenic thyroid disease may pose more of a risk for patients in older age groups (1,13), older patients seem to be at similar, or even greater risk, of being treated with larger doses of LT4 (14), or of not being treated to an appropriate thyrotropin (TSH) goal (5,7). There is also evidence that LT4 may be prescribed more frequently in the elderly (5,7), and that there is a trend over time to initiate LT4 treatment with lesser degrees of TSH elevation in patients of all age groups (11,15).…”
Section: Introductionmentioning
confidence: 99%